2015
DOI: 10.1016/j.renene.2015.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and parametric optimum design of a syngas molten carbonate fuel cell and gas turbine hybrid system

Abstract: a b s t r a c tA novel model of the molten carbonate fuel cell (MCFC) and gas turbine (GT) hybrid system with direct internal reforming is established, where the fuel cell and the auxiliary burner are taken as the heat reservoirs of the GT. Expressions for the power output and efficiency of the hybrid system are derived by considering various irreversible losses resulting from the overpotentials in the MCFC, the heat leakage in the auxiliary burner, and the finite-rate heat transfer and compression, expansion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Their analyses revealed that the incorporation of the ORC with the MCFC-GT system results in improvement in the system exergetic efficiency by 5%. Zhang et al [3] did investigation on syngas-fuelled system made of MCFC-GT. Their study showed that maximum power out of the system is obtained at fuel utilization factor 0.78.…”
Section: Introductionmentioning
confidence: 99%
“…Their analyses revealed that the incorporation of the ORC with the MCFC-GT system results in improvement in the system exergetic efficiency by 5%. Zhang et al [3] did investigation on syngas-fuelled system made of MCFC-GT. Their study showed that maximum power out of the system is obtained at fuel utilization factor 0.78.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] fuel cellheat engine, in refs. [16][17][18][19][20][21][22][23][24][25] fuel cell-Brayton, in refs. [26,27] fuel cell-Braysson hybrid systems were investigated for different conditions and performance criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization of FCs is one of the aforementioned approaches which recovers rejected heat of high temperature to enhance the overall performance. Various arrangements of FC‐heat engines setups are feasible . SOFC and MCFC which operate at high temperatures are more suitable for these purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Various arrangements of FC-heat engines setups are feasible. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] SOFC and MCFC which operate at high temperatures are more suitable for these purposes. Zhang et al 37 designed a model for a hybrid MCFC-heat engine setup, and evaluated the effective parameters on the system efficiency.…”
Section: Introductionmentioning
confidence: 99%